2020
DOI: 10.1002/oby.23054
|View full text |Cite
|
Sign up to set email alerts
|

Completeness of Intervention Reporting of Clinical Trials Published in Highly Ranked Obesity Journals

Abstract: Objective: Randomized controlled trials (RCTs) play a crucial role in the research and advancement of medical treatment. A cross-sectional study design was utilized to analyze the completeness of intervention reporting using the Template for Intervention Description and Replication (TIDieR) checklist and to evaluate factors associated with intervention reporting. A comparison of the completeness of intervention reporting before and after the publication of TIDieR was sought. Methods: PubMed was searched for RC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Second, the coding of the RGBs relied upon authors to clearly provide information upon which to judge their presence/absence. A recent study found only 12 of 200 randomized controlled trials (RCT) provided sufficient information about who delivered the intervention 39 . Other aspects of intervention reporting, such as the location of where the intervention occurred, are also poorly detailed in published RCTs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the coding of the RGBs relied upon authors to clearly provide information upon which to judge their presence/absence. A recent study found only 12 of 200 randomized controlled trials (RCT) provided sufficient information about who delivered the intervention 39 . Other aspects of intervention reporting, such as the location of where the intervention occurred, are also poorly detailed in published RCTs.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found only 12 of 200 randomized controlled trials (RCT) provided sufficient information about who delivered the intervention. 39 Other aspects of intervention reporting, such as the location of where the intervention occurred, are also poorly detailed in published RCTs. The ambiguousness or absence of this information makes identification of the RGBs difficult.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Previous obesity research has examined the completeness of intervention reporting, 29 yet no study has analysed the relevance of specific taxonomies in obesity literature. Prior to the creation of behavioural change taxonomies, there was no standardization of weight loss techniques and inconsistent reporting of results.…”
Section: Introductionmentioning
confidence: 99%
“…The reporting of source characteristics within intervention reports using these brief guidelines is often poor. For example, specification of intervention providers was found to be one of four areas requiring improvement in obesity interventions ( Rauh et al , 2021 ). We currently lack a method for specifying characteristics of an intervention’s source within behaviour change interventions.…”
Section: Introductionmentioning
confidence: 99%